The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/etc.4341
|View full text |Cite
|
Sign up to set email alerts
|

Screening‐level risk assessment of methylmercury for non‐anadromous Arctic char (Salvelinus alpinus)

Abstract: Non‐anadromous forms of Arctic char (Salvelinus alpinus), those that are restricted to lakes and rivers, typically have higher mercury (Hg) concentrations than anadromous forms, which migrate to and from the sea. Using tissue burden data from the literature and our own analyses, we performed a screening‐level risk assessment of methylmercury (MeHg) for non‐anadromous Arctic char. Our assessment included 1569 fish distributed across 83 sites. Site‐specific mean total Hg concentrations in non‐anadromous Arctic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
5
7
0
Order By: Relevance
“…Notably, THg in blood, muscle, liver, and brain of landlocked Arctic char is present almost exclusively as MeHg (Lescord et al 2015; Basu 2017), demonstrating that THg is an excellent proxy for more costly MeHg analyses. Though we sampled only 8 populations for the present study, the range in mean muscle [THg] was similar to that reported for 83 nonanadromous populations of Arctic char (Barst et al 2019). As a result, we suggest that DBS can be used to estimate [THg] in muscle, liver, and brains of Arctic char (by using the linear regression equations herein) with a high level of confidence across a wide range of [THg].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Notably, THg in blood, muscle, liver, and brain of landlocked Arctic char is present almost exclusively as MeHg (Lescord et al 2015; Basu 2017), demonstrating that THg is an excellent proxy for more costly MeHg analyses. Though we sampled only 8 populations for the present study, the range in mean muscle [THg] was similar to that reported for 83 nonanadromous populations of Arctic char (Barst et al 2019). As a result, we suggest that DBS can be used to estimate [THg] in muscle, liver, and brains of Arctic char (by using the linear regression equations herein) with a high level of confidence across a wide range of [THg].…”
Section: Discussionsupporting
confidence: 73%
“…The remaining lakes (Small, Meretta, Resolute, North, Char, and Amituk) are located on Cornwallis Island, Nunavut (Figure 1). Arctic char from these lakes have been sampled as part of past contaminant monitoring efforts, and mean muscle [THg] are known to span a wide range across the populations (Barst et al 2019). We present details of sample collection sites and the numbers of landlocked Arctic char captured from each lake in Supplemental Data, Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-migratory, or landlocked Arctic char (Salvelinus alpinus) are excellent biomonitors for freshwater ecosystems in the Arctic, because they are long-lived aquatic top predators, remain in a single ecosystem, are sensitive to environmental changes, and are a minor but dependable food source for some Arctic communities (Power et al, 2012, Barst et al, 2018.…”
Section: Accepted Manuscriptmentioning
confidence: 99%